RELASI MAKNA DALAM PUISI YANG SEDARI TADI DUDUK MEROKOK DI HADAPANMU KARYA HERWAN FR - Euis Khaeryana; Nazwa Dwi Amalia; Dodi Firmansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research analyzes the relationship between the meanings of synonyms and antonyms in a collection of poems entitled "The One That Was Smoking in Your Face" by Herwan FR. This relaxation of meaning can take the form of changes in opposite meanings (antonyms), similarities (synonyms), double meanings (polysemy), or differences in meaning (homonyms). Antonyms are relationships between words that are contradictory or opposite in meaning. Meanwhile, synonyms are meaning relationships between words, phrases or sentences that have the same or similar meaning, even though the forms are different. This research was carried out using a qualitative research method, this method was carried out by producing descriptive data in the form of written or spoken words in the collection of poems that have always been sitting in front of you. The words included in a line of poetry that select synonymous and antonymous relationships are used as data studied by researchers. In this research, researchers used three techniques, namely library techniques, listening techniques, and note-taking techniques. The data obtained is then processed by recording and selecting words that contain antonym and synonym meaning relationships. Herwan FR's poetry collection "The One Who Was Sitting Smoking in Front of You" explores contemplative themes that reflect social phenomena and everyday life. This book functions as a reflection and invitation to think further about human feelings and the environmental conditions around us. Keywords: Meaning Relations, Antonyms, Synonyms